Creativity and working knowledge: what healthcare managers can learn from architects. Issue 2 (30th June 2020) - Cranfield, Steven
Abstract : Purpose: The purpose of this paper is to describe a qualitative observational study of how middle managers in healthcare in the UK on a work-based masters programme in leadership were introduced to foundational aspects of creativity and delivering innovation through an assignment on contemporary architectural design. Design/methodology/approach: The assignment involved individual research of a recent architectural design followed by group poster presentations of findings and structured analysis. No prior knowledge of design was required. An activity theory approach was used to explore common principles of creativity and leading innovation, key features of design processes and tools for facilitating implementation. Findings: A total of 89 managers in seven cohorts completed the assignment. Data from process records and group work, artefacts and follow-up evaluation questionnaires were analysed within an interpretive approach. Analysis of data lent support for the view that exploring architectural design as an activity system helped participants to develop conceptual and applied links between management performance, creative collaboration and delivering innovation in their own, different field of practice. Where participants expressed limited self-efficacy regarding the capacity for fostering creativity, this was usually ascribed to systemic inhibitors. Practical implications: Exploring architectural design could provide a relatively low-cost, highly stimulating component of management development programmes seeking to harness the contribution of creative industries to foster work-based creativity and innovation. Originality/value: This study explores a novel use of architectural design within the context of work-applied development programmes for healthcare managers.